Developments in acoustics for studying wave-driven boundary layer flow and sediment dynamics over rippled sand-beds. (15th August 2018) - Thorne, Peter D.; Hurther, David; Cooke, Richard D.; Caceres, Ivan; Barraud, Pierre A.; Sánchez-Arcilla, Agustín
Abstract: The processes of sediment entrainment, transport, and deposition over bedforms are highly dynamic and temporally and spatially variable. Obtaining measurements to understand these processes has led to ongoing developments in instrumentation for studying near-bed sediment dynamics, with the outputs applied to the development and assessment of sediment transport modelling. In the present study results are reported from three acoustic systems deployed to make observations of bedforms, bedload, suspended concentration and horizontal and vertical velocity components. To evaluate the instruments a series of near-bed boundary layer measurements were collected in a large scale flume facility over a rippled bed of medium sand under regular waves. The observations were conducted as part of Joint Research Activities within the EU funded Hydralab project. The suite of acoustic instruments consisted of a Bedform And Suspended Sediment Imager, BASSI, a three dimensional acoustic ripple profiler, 3D-ARP, and three Acoustic Concentration and Velocity Profilers, ACVP's. Here results are reported from the deployment of the instruments, to illustrate the ongoing developments in acoustics and the expanding capability of the application of acoustics to the study of near-bed flow and sediment dynamics. Highlights: Acoustic developments for measuring boundary layer sediment processes. Measurements of flow, bedload, bedforms, and suspended load above sandy rippled beds. Assessment of horizontal fluxes decomposed into current, wave and turbulence. Partition of vertical fluxes into wave, turbulent and depositional components. Estimates of wave, turbulent and depositional sediment diffusivities.